PENERAPAN PENGORGANISASIAN DAN PEMBERDAYAAN MASYARAKAT PADA POSYANDU LANSIA DI POSYANDU KAMBOJA DESA TUNTUNGAN II - Eka Cahyani; M. Iqbal Firdaus Matondang, M. Iqbal Haqiqi Zein, Rani Suraya (Jurnal Kesehatan, 2025)
The Cambodian Elderly Posyandu Program in Tuntungan II Village aims to improve the health and welfare of the elderly through routine health checks, counseling, and elderly exercise. This study used a qualitative descriptive method, namely by conducting direct observations and interviews to collect data on program implementation. Data were analyzed using thematic techniques. The interviewed sources included the head of the posyandu, posyandu cadres, and the local community. The results showed that this program was successful in improving the health of the elderly and strengthening social relationships between participants. Although it went well, further evaluation is needed to identify potential improvements and developments. Program funding comes from the Village Fund Allocation (ADD). Overall, this program provides significant benefits and can be used as a model for similar programs in other areas, with ongoing development to expand its scope and effectiveness.